Comparative study between clinical diagnosis using modified Alvarado score and ultrasound imaging in decreasing negative appendectomy rate - Samudre, Sayali S.; Munde, Anil S. (International Surgery Journal, 2021)
Background: Acute appendicitis is the acute inflammation of appendix which is the most common cause of acute surgical emergencies. Appendicitis can mimic other pathologies. Removing normal appendix is an economical burden both on patients and health resources. Misdiagnosis and delay in surgery can lead to complications like perforation and finally peritonitis. Methods: This was prospective comparative study carried out in 200 patients over the period of 2 years. Patients with clinical features of acute appendicitis and fitting in inclusion and exclusion criteria were selected. Detailed history was noted and clinical examination was done. Necessary investigations were done, modified Alvarado score was calculated and all were subjected to ultrasonography of abdomen and pelvis. Intra operative findings were noted about nature of appendix and histopathology findings were noted. Results: The sensitivity of ultrasound is 78.19% and specificity is 50%. The sensitivity of modified Alvarado scoring system is 78.7% and specificity is 25%. Negative appendicectomy rate in the study was 6%. Conclusions: Modified Alvarado score has slightly higher sensitivity and ultrasound imaging has higher specificity of in the diagnosis of acute appendicitis and in decreasing negative appendicectomy rates. Ultrasound imaging provides good supportive diagnosis in cases of low or equivocal modified Alvarado scores.